Bangladesh : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bangladesh. (IMF Staff Country Reports; Country Report ;, 2022)
Since independence, Bangladesh has achieved impressive economic growth and social development, making steady progress in reducing poverty and significant improvements in living standards. The COVID-19 pandemic interrupted this long period of robust economic performance, deepening some earlier vulnerabilities. Stagnating job growth, rising inequality, and slowing poverty reduction remain challenges. Revenues are low, and financial sector vulnerabilities continue to be high. Substantial productive investment in infrastructure, human capital, and climate resilience is needed to achieve the authorities' aspiration to reach the upper-middle income status in 2031.